The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/jpm12071139
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Subclinical Vascular Disease in Diabetic Kidney Disease: A Tool for Personalization of Management of a High-Risk Population

Abstract: Background: Patients with diabetic kidney disease (DKD) are at increased risk for cardiovascular events but traditional risk factors do not fully explain this association. Evaluation of subclinical vascular disease might improve risk stratification and management of these patients. The aim of the study was to compare the prevalence of markers of arterial stiffness, carotid atherosclerosis and peripheral arterial disease between patients with DKD and patients with type 2 diabetes mellitus (T2DM) and preserved k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…11,13 In contrast, CKD usually causes distal involvement in uremia via vascular calcification, which was demonstrated to be attributable to the osteogenic differentiation of vascular smooth muscle cells. 11 Our results are consistent with those of Kourtidou et al 26 who found that DM and CKD are independently associated with PAD. Keller et al 27 who reviewed profiles and outcomes of hospitalized patients with PAD revealed an unfavorable association with DM, including a higher risk of adverse events, higher amputation rates, and higher hospital mortality.…”
supporting
confidence: 92%
“…11,13 In contrast, CKD usually causes distal involvement in uremia via vascular calcification, which was demonstrated to be attributable to the osteogenic differentiation of vascular smooth muscle cells. 11 Our results are consistent with those of Kourtidou et al 26 who found that DM and CKD are independently associated with PAD. Keller et al 27 who reviewed profiles and outcomes of hospitalized patients with PAD revealed an unfavorable association with DM, including a higher risk of adverse events, higher amputation rates, and higher hospital mortality.…”
supporting
confidence: 92%
“…Previous studies focused on the cardiovascular risk profile of patients with DKD; Kourtidou et al have recently reported that patients with DKD appear to have higher arterial stiffness and carotid atherosclerosis than patients with type 2 diabetes and preserved kidney function [ 23 ]; other authors have reported a relationship between IMT, vascular function, eGFR and stages of diabetic nephropathy [ 24 , 25 ]. However, none of these studies evaluated markers of cardiovascular disease in different phenotypes of DKD, to identify in which of them the cardiovascular risk is greater.…”
Section: Discussionmentioning
confidence: 99%
“…Methods have been reported in detail previously [ 20 ]. In brief, this is a prespecified analysis of a cross-sectional study in which we enrolled all adult patients with diabetic kidney disease (DKD) [ 21 ] who visited the Internal Medicine Outpatients Clinic of the First Propedeutic Department of Internal Medicine between August 2021 and April 2022.…”
Section: Methodsmentioning
confidence: 99%